Self–Monitoring, Self–Policing, Self–Incrimination and Pollution Law. - Howarth, William (Modern Law Review, 1997)
Focuses on the criminal proceedings for water pollution offenses and other kinds of environmental crime in Great Britain. Administrative background of the environment agency; Pollution law enforcement policy; Water sampling requirements; Evidence of water quality.